In INGOs we trust? How individual determinants and the framing of INGOs influences public trust. Issue 6 (17th August 2020) - Davis, John-Michael; Henson, Spencer; Swiss, Liam
ABSTRACT: Recent scandals in the media have questioned the legitimacy of and public trust in international NGOs (INGOs). Yet, little research has explored the complex relationships that influence public trust in INGOs. This article addresses this knowledge gap by analysing data from an experimental survey of English-speaking Canadian residents to explore how trust varies based on the different ways INGOs are framed and the individual determinants that influence public trust. The results reveal critical factors influencing the trust of Canadians in INGOs and inform strategies to regain public trust to safeguard their role on the world development stage.